KONTRIBUSI ISTRI PEMBUDIDAYA RUMPUT LAUT DI KABUPATEN WAKATOBI - Rosmawati Rosmawati; Roslindah Daeng Siang; Hasnia Arami; Nurhuda Annaastasia (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2022)
Seaweed cultivation is a source of livelihood for the community which involves the wife in its activities. This study aims to determine the contribution of the wife's income and the wife's time spent working on seaweed cultivation business activities. This study uses a qualitative descriptive analysis method. The results of this study can describe the profile of the fishermen's wives in the seaweed cultivation business based on age, level of education and business experience. The wife's income from seaweed cultivation activities contributes to family income which is still in the moderate category of 43%, but the family income earned in Wangi-Wangi District, Wakatobi Regency is classified as above the UMR (Regional Minimum Wage) Southeast Sulawesi. The wife's labor time spent working to earn a living in the seaweed cultivation business is an average of 4.42 hours and as much as 20.106 HOK (Working Day) per week in each activity of the seaweed production process per cycle.Keywords: Income Contribution, fisherman’s wife, E. spinosum, E. cottonii